Effects of combined application of pig manure composts prepared using different fermentation methods with chemical fertilizer on winter wheat yield, light-thermal physiology, and soil biological characteristics - Wang, Mingteng; Cai, Jiaming; Zeng, Chong; Li, Meng; Wang, Yilun; Geng, Sainan; Li, Gang; Li, Lantao (Frontiers in Plant Science, 2025)
PurposeThis study examined the effects and underlying mechanisms of combining pig manure composts, produced by different fermentation methods, with chemical fertilizers on winter wheat yield, nutrient uptake, light–thermal physiology, soil fertility, and microbial communities.MethodsField experiment was conducted in Yuanyang County, Henan Province (2023–2024) with the following treatments: no fertilizer (CK), chemical fertilizer (TK), combined organic–inorganic applications with 25:75 and 50:50 ratios. The 25:75 treatments included natural compost (TA1), water-controlled trough compost (TA2), acid-controlled trough compost (TA3), and trough compost (TA4) combined with chemical fertilizer; the 50:50 treatments included the same four compost types (TB1–TB4). Their effects on yield, nutrient uptake dynamics, and light–thermal traits were evaluated, alongside changes in soil physicochemical properties, available nitrogen distribution, aggregate structure, enzyme activities, and microbial community composition and diversity.ResultsThe compost-to-fertilizer ratio of 25:75 significantly increased yields, with TA3 performing best—42.26%, 6.43% and 12.68% higher than the CK, TK, and the average of other organic fertilizer treatments, respectively. TA3 also recorded the highest total nitrogen, phosphorus, and potassium uptake and the greatest average uptake rate. It markedly enhanced photosynthetic performance at all growth stages. Compost–fertilizer combinations improved soil nutrient levels and increased the proportion of large aggregates (≥0.25 mm). High-throughput sequencing revealed that acid-regulated compost altered microbial community structure and promoted the expansion of rare taxa. Moreover, partial least squares path model indicated that acid-regulated trough compost increased yield by elevating soil nutrient levels and improving wheat physiological status.Conclusion25:75 acid-regulated compost–fertilizer combination significantly improved winter wheat yield, nutrient efficiency, light–thermal use, soil fertility, structure, and microbial diversity, providing a practical basis for efficient organic fertilizer use in sandy fluvo-aquic soils of China’s winter wheat regions.